(untitled) (Jurnal Bahasa, 2003)
Dialect is a variation or language differences spoken by a group of speakers according to the different geographical area. In, Malaysia, the language variation shows an unevenness in its usage. This article aims to investigate and scrutinize the variation from Perak dialect, i.e. sub-dialect of Kuala Kangsar. From the research, this sub-dialect shows a mixture of dialect criteria from outside and foreign dialects. As a whole, this condition shows a uniqueness in Perak dialect with an overlap linguistic phenomenon. This had made Kuala Kangsar as a zone of dialect transition and can still retain the pureness of Perak dialect.